Penerapan Metode SAVI dalam Menyimak Dongeng Anak Tunagrahita SDN Pondok Aren 01 Tangerang - Sulistyawati, Tia; Fadhilla, Aisya Rahma (Indonesian Journal of Islamic Elementary Education, 2023)
This research was conducted with the aim of solving the problems faced by teachers in dealing with elementary school students with special needs, namely the mentally impaired. The method used in research from the results of literature reviews in the form of accredited books and scientific journals as well as mini research and observation to elementary schools as supporting data to deal with students with intellectual disabilities is using the SAVI Method in learning Indonesian language material for listening to fairy tales with multi-sensory. The results of this study revealed that the SAVI method is effectively used to overcome learning difficulties, especially in Indonesian learning, namely listening. In this case, the teacher as the spearhead to better direct students in the learning process so that the expected goals can be achieved optimally. The SAVI method, which is applied using four implementation steps (preparation stage, delivery stage, training stage, and performance stage), is considered to be effective for children experiencing learning difficulties in listening to fairy tales, both for students with intellectual disabilities and for normal students.